A FFAR1 full agonist restores islet function in models of impaired glucose-stimulated insulin secretion and diabetic non-human primates - Rady, Brian; Liu, Jianying; Huang, Hui; Bakaj, Ivona; Qi, Jenson; Lee, S. P.; Martin, Tonya; Norquay, Lisa; Player, Mark; Pocai, Alessandro (Frontiers in Endocrinology, 2022)
The free fatty acid receptor 1 (FFAR1/GPR40) mediates fatty acid-induced insulin secretion from pancreatic β-cells. At least 3 distinct binding sites exist on the FFAR1 receptor and numerous synthetic ligands have been investigated for their anti-diabetic actions. Fasiglifam, binds to site-1 and stimulates intra-cellular calcium release and improves glycemic control in diabetic patients. Recently, small molecule FFAR1 agonists were discovered which bind to site-3, stimulating both intra-cellular calcium and cAMP, resulting in insulin and glucagon-like peptide-1 (GLP-1) secretion. The ability of our site-3 FFAR1 agonist (compound A) to control blood glucose was evaluated in spontaneously diabetic cynomolgus monkeys during an oral glucose tolerance test. In type-2 diabetic (T2D) animals, significant reductions in blood glucose and insulin were noted. To better understand the mechanism of these in vivo findings, we evaluated the effect of compound A in islets under several conditions of dysfunction. First, healthy human and non-human primate islets were treated with compound A and showed potentiation of insulin and glucagon secretion from both species. Next, we determined glucose-responsive insulin secretion under gluco-lipotoxic conditions and from islets isolated from type-2 diabetic humans. Despite a dysfunctional phenotype that failed to secrete insulin in response to glucose, site-3 FFAR1 agonism not only enhanced insulin secretion, but restored glucose responsiveness across a range of glucose concentrations. Lastly, we treated ex vivo human islets chronically with a sulfonylurea to induce secondary beta-cell failure. Again, this model showed reduced glucose-responsive insulin secretion that was restored and potentiated by site-3 FFAR1 agonism. Together these data suggest a mechanism for FFAR1 where agonists have direct effects on islet hormone secretion that can overcome a dysfunctional T2D phenotype. These unique characteristics of FFAR1 site-3 agonists make them an appealing potential therapy to treat type-2 diabetes.